Fractures in users of antidepressants and anxiolytics and sedatives: effects of age and dose. - Vestergaard, P; Prieto-Alhambra, D; Javaid, M; Cooper, C (2013)
SUMMARY: Antidepressants have been associated with fractures. In a case-control study, increasing age was associated with more fractures in users of selective serotonin reuptake inhibitors and tricyclic antidepressants, whereas for anxiolytics and sedatives, more fractures were seen among the younger users. Depression per se did not seem associated with fractures. INTRODUCTION: This study aims to study the effects of age and dose of selective serotonin reuptake inhibitors (SSRI), tricyclic antidepressants (TCA) and anxiolytics/sedatives on fracture risk. METHODS: The study was designed as a case-control study. From the Danish National Health Service, we identified 124,655 fracture cases and 373,962 age- and gender-matched controls. Crude odds ratios were estimated, and propensity score adjustment was used to minimise confounding by indication. RESULTS: A higher risk of fractures was associated with an increasing dose of anxiolytics and sedatives; the highest excess risk was present in the age stratum below 40 years of age (p < 0.01), and thereafter, the excess risk of fractures declined with age. For SSRI, a growing excess risk of fractures was seen with both increasing dose and age. Regarding TCA, no particular trend with age was present. However, an increasing risk of fractures was associated with increasing TCA dose in the age group above 60 years. Finally, for other antidepressants, no particular trend with age or dose was observed. In our data, a hospital diagnosis of depression or manic depression was associated with fewer fractures. CONCLUSION: Caution should be shown upon prescription of SSRI to older subjects. A hospital diagnosis of depression or manic depression and thus potentially a more severe disease was not a risk factor for fractures.